Lateral Si0.15Ge0.85/Ge/Si0.15Ge0.85 Double-Heterojunction Laser With SiN Stressor - Xinyang Sun; Bin Shu; Huiyong Hu (IEEE Photonics Journal)
Integrated circuit technology has undergone significant advancements and progress over the past few decades. However, as the demand to further shrink circuit sizes increases, traditional IC interconnections face challenges such as RC delay, energy loss, and interconnect interference, which become increasingly prominent. Optical interconnection emerges as a promising solution to mitigate these issues by enabling reductions in circuit size, power consumption, and signal delay. In this article, we propose a novel lateral Si0.15Ge0.85/Ge/Si0.15Ge0.85 p-i-n double-heterojunction laser array, leveraging SiN stress as a key component. Our study focuses on the EL emission properties of individual lasers within the array, the distribution of SiN stress within the device, and the impact of stress on the laser properties. Additionally, we design a Si0.15Ge0.85/SiO2 distributed Bragg reflector (DBR) tailored for the laser array. Simulation results demonstrate a peak luminescence wavelength of 1849 nm and a threshold current density of 190 kA/cm2 at 300 K.